Derivation of porcine extraembryonic endoderm‐like cells from blastocysts - Li, Yan (Cell Prolif, 2020)
OBJECTIVES: Extraembryonic endoderm (XEN) cells are isolated from primitive endoderm (PrE) of blastocysts. Just like PrE, XEN cells have the ability to differentiate into parietal endoderm (PE) and visceral endoderm (VE), and therefore, they are useful tools for studying mechanisms of PrE cells development and differentiation. Pig is an ideal model for studying human cardiovascular and metabolic diseases and a potential organ source for allotransplantation, while no XEN cell has been obtained from porcine embryos. MATERIALS AND METHODS: Using a serum‐free culture system, we directly derived porcine extraembryonic endoderm‐like cells (pXEN‐like cells) from day 6‐7 blastocysts, which could maintain self‐renewal for at least 30 passages. RESULTS: The pXEN‐like cells resembled mouse XEN cells with large and flat clone morphology and expressed XEN marker genes but not pluripotent genes. Upon in vitro induction, the cells could differentiate into VE and PE. FGF/MEK signalling was not only essential for the maintenance of pXEN‐like cells, but also the induction of pXEN‐like cells from porcine embryonic stem (pES) cells. CONCLUSIONS: We directly obtained cell lines with XEN characteristics from porcine embryos for the first time. The cells will be helpful tools for studying embryonic development and cell differentiation, which also represent promising cell sources for human regenerative medicine.